Foreing experience of model juvenile justice system functionining - Tereshchuk, Galina (Actual problems of law (Aktual'ni problemi pravoznavstva), 2018)
The article analyzes the main features of the model juvenile justice system prevailing in the Anglo-Saxon, continental and Scandinavian countries and their importance at the present stage of implementation of restorative justice for juveniles.